FAKTOR-FAKTOR YANG MEMPENGARUHI REALISASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH PADA DINAS ESDM PROVINSI NUSA TENGGARA TIMUR - Yolanda O.M. Widyasari; Theresia Fouk Leu (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
Yolanda Widyasari and Theresia Fouk Leu. 2024. Factors Influencing Regional Budget Realization at the NTT Provincial Energy and Mineral Resources Office. The research problem is the Regional Budget (APBD) has not reached the target, and the unknown factors. The research objective is to determine the factors influencing APBD realization. The research type is descriptive, with data collection techniques using interviews and documentation. The data analysis technique is descriptive qualitative. The results show that the NTT Provincial ESDM Office's budget absorption is below 95%. This is influenced by several factors, delays in work schedules, budget implementation factors for construction, several activities that still need to be reviewed due to discrepancies between drawings and budget documents. Procurement of goods/services in the field often encounters obstacles due to documents submitted by the SIKI (construction information system) provider not meeting requirements or being no longer valid. Mismatched raw materials, raw materials still undergoing laboratory testing, and management commitment. It is recommended that the NTT Provincial Energy and Mineral Resources Office optimize budget absorption and implement stricter oversight of budget implementation. Furthermore, the procurement of goods and services should be closely monitored. This will impact commitments in the field. If the procurement process is not in line with existing commitments, it will impact the performance of the local government.